PERSEPSI SISWA TERHADAP MAKNA KEHADIRAN GURU DI TENGAH PENGGUNAAN TEKNOLOGI PEMBELAJARAN - Ainur Rofiqoh; Kholilatul Fauziah; Arief Rahman Hakim; Anisya Khaerani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid advancement of learning technology is driving fundamental changes in educational processes. Amid the ease of accessing information through various digital platforms, a fundamental question arises regarding how students perceive the meaning of teachers' presence. This study aims to explore students' perceptions across various educational levels regarding the role and significance of teachers' presence in the era of learning technology. A qualitative research method was employed in this study. The findings indicate that students continue to regard teachers' presence as an irreplaceable element, particularly in emotional, moral, and motivational aspects that technology cannot fulfill. This study contributes to the understanding of teacher-student relationships in the digital era and provides implications for the development of educational policy.